Analysis Of Figurative Language In Three Poems By Robert Frost - Praja Nur Ichsan; Ammar Muhammad Ra’id Zhafir Nur Haqiqi Riyadi (STIKes Ibnu Sina Ajibarang, 2024)
This research examines how Robert Frost uses metaphorical language in three of his well-known poems: